The Role of Corporate Governance as a Moderating Variable on Earnings Management and Carbon Emission Disclosure - Astari, Ayu; Saraswati, Erwin; Purwanti, Lilik (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
The purpose of this study is to examine the influence of earnings management on carbon emission disclosure with corporate governance as a moderating variable. The population was companies in the sector of industry and chemical, agriculture, energy, transportation listed on the Indonesia stock exchange (IDX). Based on the purposive sampling method, 12 companies were selected as the samples (60 firm-year observations). The data analysis technique used is the moderate regression analysis (MRA). The results showed that the earnings management has a significant positive effect on carbon emission disclosure. The board of commissioner size moderates the influence of the earnings management on the carbon emission disclosure. The board of directors has a role in affecting the carbon emission disclosure, while the independent commissioners, the institutional ownership, and the audit committee meetings do not have a significant effect on weakening the effect of profit management on carbon emission disclosure